Learning object repositories as knowledge management systems - Sampson, Demetrios; Zervas, P. (2013)
Over the past years, a number of international initiatives that recognize the importance of sharing and reusing digital educational resources among educational communities through the use of Learning Object Repositories (LORs) have emerged. Typically, these initiatives focus on collecting digital educational resources that are offered by their creators for open access and potential reuse. Nevertheless, most of the existing LORs are designed more as digital repositories, rather than as Knowledge Management Systems (KMS). By exploiting KMSs functionalities in LORs would bare the potential to support the organization and sharing of educational communities' explicit knowledge (depicted in digital educational resources constructed by teachers and/or instructional designers) and tacit knowledge (depicted in teachers' and students' experiences and interactions of using digital educational resources available in LORs). Within this context, in this paper we study the design and the implementation of fourteen operating LORs from the KMSs' perspective, so as to identify additional functionalities that can support the management of educational communities' explicit and tacit knowledge. Thus, we propose a list of essential LORs' functionalities, which aim to facilitate the organization and sharing of educational communities' knowledge. Finally, we present the added value of these functionalities by identifying their importance towards addressing the current demands of web-facilitated educational communities, as well as the knowledge management activities that they execute.